Low-Voltage Operation and Lithium Bis(trifluoromethanesulfonyl)imide Electrolyte Salt Enable Long Li-Ion Cell Lifetimes at 85 °C. Issue 10 (1st October 2022) - Taskovic, T.; Eldesoky, A.; Aiken, C. P.; Dahn, J. R.
Abstract : LiFePO4 /graphite (LFP), Li[Ni0.5 Mn0.3 Co0.2 ]O2 /graphite (NMC3.8 V, balanced for 3.8 V cut-off), and Li[Ni0.83 Mn0.06 Co0.11 ]O2 /graphite (Ni83, balanced for 4.06 V cut-off) cells were tested at 85 °C. Three strategies were used to improve cell lifetime for all positive electrode materials at 85°C. First, low voltage operation (<4.0 V) was used to limit the parasitic reactions at the positive electrode. Second, LiFSI (lithium bis(trifluoromethanesulfonyl)imide) was used as the electrolyte salt for its superior thermal stability over LiPF6 (lithium hexafluorophosphate). The low voltage operation avoids the aluminum corrosion seen at higher voltages with LiFSI. NMC3.8 V cells were operated at 6 C charge and 6 C discharge without issue for 2500 cycles and then moved to room temperature where normal operation was obtained. Finally, dimethyl-2, 5-dioxahexane carboxylate (DMOHC) was used as a sole electrolyte solvent or mixed with dimethyl carbonate. μ -XRF data showed no detectable levels of transition metal deposition on the negative electrode of Ni83 and LFP cells, and DMOHC cells showed less gassing after testing compared to EC-based electrolytes. We found incredible capacity retention and cycle life for Ni83 and NMC3.8 V cells using DMOHC and LiFSI at 70 °C and at 85 °C in tests that ran for more than 6 and 5 months (and are still running), respectively.